2020
DOI: 10.1080/20013078.2020.1790159
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐ and cytokine‐associated extracellular vesicles mediate squamous cell carcinomas

Abstract: Exosomes, or small extracellular vesicles (sEVs), serve as intercellular messengers with key roles in normal and pathological processes. Our previous work had demonstrated that Dsg2 expression in squamous cell carcinoma (SCC) cells enhanced both sEV secretion and loading of pro-mitogenic cargo. In this study, using wild-type Dsg2 and a mutant form that is unable to be palmitoylated (Dsg2cacs), we investigated the mechanism by which Dsg2 modulates SCC tumour development and progression through sEVs. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 58 publications
1
65
0
Order By: Relevance
“…We recently demonstrated that the membrane protein desmoglein 2 (Dsg2) modulates sEV biogenesis through the endocytic pathway (Overmiller et al, 2017;Flemming et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that the membrane protein desmoglein 2 (Dsg2) modulates sEV biogenesis through the endocytic pathway (Overmiller et al, 2017;Flemming et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, associations between DSG2 and IL-8 have been demonstrated in patients with HNSCC. Furthermore, the oncogenic ability of DSG2 in SCC was correlated with the EV level [87]. These results suggest that intercellular communication can be coordinated through the secretion of DSG2 and EVs, critical for tumor growth, and may serve as a potential biomarker to guide treatment regimens.…”
Section: Desmosome Cadherins Act As An Oncogene In Hncmentioning
confidence: 76%
“…The palmitoylation of DSG2 alters the trafficking of membrane raft proteins and early endosomal proteins. In the xenograft model, DSG2 promoted tumor growth and reduced this effect considerably with overexpression of non-palmitoylated DSG2 in cells [87]. These phenomena suggest that the post-translational modification of desmosomal cadherins is crucial in deciding its role in HNC.…”
Section: Ptm and Subcellular Locations Of Desmosomal Cadherinsmentioning
confidence: 86%
“…Kai et al showed that DSG2 expression is increased in lung cancer, and decreased regulation could suppress tumor growth [26]. Similarly, Barber et al, Abulrob et al, Plus Kamekura et al found that DSG2 de ciency leads to inhibition of cell proliferation and tumor growth in colon epithelial cancer [27][28][29]. Shuhang showed that desmoglein 2 is a biomarker that causes tumor proliferation and metastasis and is associated with a poor prognosis in the early stages of cervical cancer [30].…”
Section: Discussionmentioning
confidence: 99%